Conductivity Studies on K-Carrageenan-Methyl Cellulose Blend as Bio-Polymer Electrolyte / Rosnah Zakaria and Ab Malik Marwan Ali - Zakaria, Rosnah; Marwan Ali, Ab Malik (Universiti Teknologi MARA Shah Alam, 2020)
Solid polymer-based electrolyte materials are a great interest due to their many interesting characteristics such as flexibility, and it is easily prepared into films with a large surface area. Two sets of k-carrageenan-methyl cellulose samples were prepared using the solution casting method. Set 1, the wt% of k-Carrageenan was fixed at 0.1 wt%, while methyl cellulose and NH4I was varied. Set 2, the wt% of methyl-cellulose was fixed to 0.1 wt%, and the carrageenan and NH4I were varied. The functional group of samples were studied using FTIR spectroscopy, and the ionic conductivity was studied using impedance spectroscopy, EIS at room temperature. FTIR spectra from set 1 show a small hump at between the 1500 cm-1 to 1000 cm-1 spectra’s which O=S=O symmetrical vibration from methyl cellulose component. This hump was shifted to higher wavenumber due to the increasing of NH4I wt% in the samples. The second region of set 2’s spectra shows the wavenumber between 2000 cm-1 to 1500 cm-1 is the deformation of H-O-H band interactions and its wavenumber decreasing as the addition of salts increasing. The third region of spectra between 1500 cm-1 to 1000 cm-1 represents the band of O=S=O symmetrical vibration. This bands shifted to the lower wavenumber due to addition of salts, and it became less intense towards salt addition. On the other hand, the best conductivity is 6.00 x 10-8 S cm-1 which belongs to B2 of set 2 with the composition of 0.3 wt% k-carrageenan with 0.1 wt% methylcellulose and 0.6 wt% NH4I salt and the lowest conductivity is 3.19 x 10-9 S cm-1 which its composition is 0.1 wt% k-carrageenan with 0.4 wt% methylcellulose and 0.5 wt% NH4I salt in sample D1 of set 1. In conclusion, the optimum component by weight percentage of k-carrageenan: methyl cellulose: NH4I is 0.3:0.1:0.6.